2010
DOI: 10.1007/s00198-010-1312-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of estrogen receptor alpha and collagen type I alpha 1 gene polymorphisms with bone mineral density in postmenopausal women

Abstract: In conclusion, it was designated that ERα gene PvuII polymorphism was effective on average lumbar vertebra BMD value in postmenopausal women of our study group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…In addition, a recent study using quantitative computed tomography (QCT) demonstrated that estrogen deficiency is closely related to bone loss in the cortical area but not in the trabecular area [33]. Meanwhile, several studies have investigated the relationship between BMD at each site and genetic polymorphisms, such as the estrogen receptor-alpha and collagen-type I alpha 1 genes [34], or the sex hormone-binding globulin gene [35]. These genome-wide association studies provide much more information about site-, age-, and gender-specific genetic effects on BMD [36].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a recent study using quantitative computed tomography (QCT) demonstrated that estrogen deficiency is closely related to bone loss in the cortical area but not in the trabecular area [33]. Meanwhile, several studies have investigated the relationship between BMD at each site and genetic polymorphisms, such as the estrogen receptor-alpha and collagen-type I alpha 1 genes [34], or the sex hormone-binding globulin gene [35]. These genome-wide association studies provide much more information about site-, age-, and gender-specific genetic effects on BMD [36].…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, some studies are in complete disagreement with the model which provides a direct FSH regulation of the bone mass [164][165][166]. The presence of direct transcriptional targets of sex steroid hormones in bone [167] and the evidence of a clear association between estrogen receptors subtypes with the features of the bone metabolism [168][169][170][171][172][173][174][175], suggest that gonadotropins and their receptors do not have a predominant role in regulating the bone turnover mechanisms. Finally, a prospective study performed on postmenopausal women treated with a GnRH agonist, demonstrated that suppression of serum FSH levels does not reduce markers of bone resorption, providing a final, strong evidence that FSH does not directly regulates bone resorption [176].…”
Section: Fshr Polymorphisms On Bonementioning
confidence: 98%
“…LS is an age-related disease based on osteoporosis. Recent studies suggest that estrogen receptor alpha and collagen type I alpha 1 gene polymorphisms are related with female osteoporosis [17]. Since LS is common in the elderly, it is difficult to determine to what extent LS contributes to urinary retention.…”
Section: Pol Scientificmentioning
confidence: 99%